A Short Comment on Controlled Context-Free Grammar Derivations - Holzer, Markus; Justus Liebig University Giessen (My University, 2024)
We prove that the family of languages generated by regularly controlled grammars with control languages accepted by ordered automata is equal to the family of languages generated by matrix grammars. To our knowledge, this equivalence has been overlooked in the literature.
Keywords: Context-Free Grammars; Controlled Derivation; Ordered Languages; Matrix Grammars and Languages; ddc:004